Sociodemographic and clinical profile of patients with pressure ulcer - Barreto, Ana Patricia Costa Paes; Araújo, Bruna Cavalcanti; Vieira, José Cristovam Martins (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to identify the sociodemographic and clinical patients inherent to patients with pressure ulcers (UPs) hospitalized in a home care hospital. Method: this is an exploratory-descriptive study, with a quantitative approach. It was carried out at the home care hospital on March 2009, through a structured interview and observation of the ulcers, whose data were organized in the software Excel 2007. The population consisted of 77 patients, being included all patients who had a PU in any stage and site. Study approved by the Ethics Committee of Hospital Agamêmnon Magalhães under the Record 11/2009, in accordance with the Resolution 196/96. Results: the sample consisted of 23 patients with pressure ulcers, with prevalence of the age group over 80 years (34.78%); males (56.57%); white-skinned (39.13%); married or widowed individuals (39.13% each); complete high school (34.78%); income from 3 to 5 minimum wages (43.47%). Regarding comorbidities, cardiovascular diseases were the most frequent, with 73.91%, there were 34.8% individuals using mechanical ventilation, and 70% of them were confined to bed. Forty-eight PUs were identified, being the sacral region the prevailing site. Conclusion: the profile was consistent with the literature, being most of them bedridden elderly patients, with chronic-degenerative diseases, and pressure ulcers. One should emphasize prevention and observation of skin. Descriptors: pressure ulcer; nursing assistance; home assistance. RESUMO Objetivo: identificar o perfil sociodemográfico e clínico inerente aos pacientes portadores de úlceras por pressão (UPs) internados em um hospital de assistência domiciliar. Método: trata-se de estudo exploratório-descritivo, com abordagem quantitativa. Realizado no hospital de assistência domiciliar em março de 2009, por intermédio de entrevista estruturada e observação das úlceras, cujos dados foram organizados no programa Excel 2007. A população constou de 77 pacientes, sendo incluídos todos os pacientes que possuíssem UP em qualquer estágio e localização. Estudo aprovado pelo Comitê de Ética do Hospital Agamêmnon Magalhães sob o Registro n.11/2009, em conformidade com a Resolução 196/96. Resultados: a amostra encontrada foi de 23 pacientes, sendo prevalente a faixa etária superior a 80 anos (34,78%); sexo masculino (56,57%); raça branca (39,13%); casados e viúvos (39,13% cada); ensino médio completo (34,78 %); renda de 3 a 5 salários-mínimos (43,47%). Quanto às comorbidades, as doenças cardiovasculares se sobressaíram com 73,91%, havia 34,8% em ventilação mecânica e 70% estavam acamados. Foram identificadas 48 UPs, sendo a região sacra o local predominante. Conclusão: o perfil foi condizente com a literatura, sendo em sua maioria idosos acamados, portadores de doenças crônico-degenerativas e de úlceras por pressão. Deve-se enfatizar a prevenção e observação da pele. Descritores: úlcera por pressão; assistência de enfermagem; assistência domiciliar. <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">RESUMEN<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 11pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">Objetivo<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">:<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">identificar<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">el perfil <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">sociodemográfico y clínico inherente a los pacientes con úlceras por presión (UPs), internados <span style="line-height: 115%; font-family: "Cambria Math","serif"; font-size: 9pt; mso-bidi-font-family: 'Cambria Math'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-ascii-font-family: 'Trebuchet MS'; mso-bidi-language: AR-SA;" lang="ES">​​<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: Calibri; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">e<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">n<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">un hospital<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">de<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">asistencia domiciliaria<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">. <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">Método<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">:<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> esto es un <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">estudio<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">exploratorio<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">-<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">descriptivo, con abordaje cuantitativo. <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">Realizado en el hospital de asistencia domiciliaria en marzo de 2009, a través de entrevista estructurada y observación de las úlceras, cuyos datos fueron organizados en el programa Excel 2007. La población incluyó 77 pacientes y incluyó todos los pacientes que tenían UP en cualquier estadio y localización. Estudio aprobado por el Comité de Ética del Hospital <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: TTFF4C4E78t00; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">Agamêmnon Magalhães<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> bajo el Registro<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">11/2009<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">, en conformidad con <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">la Resolución<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">196/96<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">. <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">Resultados<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">:<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; color: windowtext; font-size: 9pt; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">la<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">muestra<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">fue de<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">23<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">pacientes<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">, siendo prevalente la franja etaria<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> mayor de<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">80 años<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">(<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">34,78%), <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">hombres<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> (<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">56,57<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">%); <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">blancos (39,13<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">%); <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">casados<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Cambria Math","serif"; font-size: 9pt; mso-bidi-font-family: 'Cambria Math'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-ascii-font-family: 'Trebuchet MS'; mso-bidi-language: AR-SA;" lang="ES">​​<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">y<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">viudos<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> (<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">39,13<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">% cada); <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> educación media completa<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> (34,78<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">%); <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">renta de 3 a 5<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">salarios mínimos<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> (<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">43,47<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">%). En c<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">uanto a<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">las comorbilidades<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">, las enfermedades cardiovasculares <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">se destaca<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">ron, <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">con<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">73,91<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">%, hubo <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">34,8%<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">en<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">ventilación<span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES"> <span style="line-height: 115%; font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="ES">mecánica<span class="longtext